2021
DOI: 10.1002/smll.202008114
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Nanozymes Based on Coassembly of Amino Acid and Hemin for Catalytic Oxidation and Sensing of Biomolecules

Abstract: Nanoassemblies based on self‐assembly of biological building blocks are promising in mimicking the nanostructures, properties, and functionalities of natural enzymes. However, it remains a challenge to design of biomimetic nanozymes with tunable nanostructures and enhanced catalytic activities starting from simple biomolecules. Herein, the construction of nanoassemblies through coassembly of an amphiphilic amino acid and hemin is reported. The nanostructures and morphologies of the resulting nanoassemblies are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
67
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(68 citation statements)
references
References 53 publications
1
67
0
Order By: Relevance
“…The characteristic peak splitting and moving at 3338 cm –1 (–OH and –NH) and 1660 cm –1 (–COOH) originates from the coordination of wool keratin with Cu 2+ through hydroxyl, sulfhydryl, amino, and carboxyl groups resulting in the disruption of the corresponding group vibrations. [ 20 ] The measured XPS spectrum of CuWK confirms the presence of Cu, O, N, C, and S (Figure S5, Supporting Information). Figure 1g showed that the binding energy peaks of Cu 2p 3/2 at 934.2 eV and Cu 2p 1/2 at 954.2 eV were assigned to Cu 2+ and are accompanied by characteristic Cu 2+ oscillating satellite peaks (961.7 eV, 940.7 eV).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…The characteristic peak splitting and moving at 3338 cm –1 (–OH and –NH) and 1660 cm –1 (–COOH) originates from the coordination of wool keratin with Cu 2+ through hydroxyl, sulfhydryl, amino, and carboxyl groups resulting in the disruption of the corresponding group vibrations. [ 20 ] The measured XPS spectrum of CuWK confirms the presence of Cu, O, N, C, and S (Figure S5, Supporting Information). Figure 1g showed that the binding energy peaks of Cu 2p 3/2 at 934.2 eV and Cu 2p 1/2 at 954.2 eV were assigned to Cu 2+ and are accompanied by characteristic Cu 2+ oscillating satellite peaks (961.7 eV, 940.7 eV).…”
Section: Resultsmentioning
confidence: 89%
“…[ 18–24 ] Especially, the fabrication of enzyme mimics based on the self‐assembly of biomolecules with metal ions has attracted enormous attention. [ 20–24 ] Self‐assembly allows biomolecules (e.g., amino acids, proteins, purines) to be combined with metal ions or artificial enzymes through non‐covalent bonding interactions to mimic natural enzyme catalytic centers more realistically. Although significant progress has been achieved in this field, only a few preliminary attempts and efforts have been made to develop metallo‐nanozymes with multiple antioxidant activities.…”
Section: Introductionmentioning
confidence: 99%
“…After pyrolysis and acid etching, the Co-Nx-NC was synthesized and applied for acetylcholinesterase detection with oxidase- and catalase-mimicking properties of Co-Nx-NC. Another example is biomimetic nanozymes for glucose detection that have been designed by Geng et al [ 180 ]. They combined amphiphilic amino acid, a histine derivative for fabricating nanoassemblies with the assistance of metal ions, and a heme derivative, which included iron ions in the center.…”
Section: Challenges and Future Directions For Nanozyme Researchmentioning
confidence: 99%
“…The construction of structurally well-defined nanoarchitectures starting from discrete nanoscale objects has become an effective strategy for developing next generation functional materials for optoelectronic devices, [3] separation, [25][26][27] energy storage, [28][29][30] and biological applications, [31] since their properties such as catalytic activity, exciton transport and electron transfer, etc., are strongly dependent on the shape, size and molecular arrangement within the assembly. [32] Creation of nanoarchitectures with different morphologies, sizes and properties is the fundamental step to realize next generation complex multi-component systems with specific properties and applications. [33][34][35][36] The new type of nanomaterials, MOP, as supramolecular building blocks, have been employed being linked by covalent bonds or coordinative linkages on the metal ions dimers, or via noncovalent self-assembly.…”
Section: Introductionmentioning
confidence: 99%